Lipid Profile in Drug Naive Hypertensive Patients visiting Cardiology OPD in a Central Hospital - Poudel , Samir Kumar; Mishra, Deepak Kumar; Gautam, Binayak; Sherpa, Kunjang; Koirala, Prabha Chapagain; Bhandari , Rajendra; Poudel, Lata Gautam (Journal of National Heart and Lung Society Nepal, 2024)
Background: Hypertension and dyslipidemia are two major risk factors for cardiovascular disease and often coexist and share common pathophysiological mechanisms. Their coexistence has a multiplicative adverse effect on cardiovascular risk. Understanding the lipid profile in drug-naive hypertensive patients is important for effective management and prevention of cardiovascular complications. The objective of the study was to assess the lipid profile in drug-naive hypertensive patients visiting the Cardiology Outpatient Department (OPD) of a central hospital. Methods: This was a prospective observational study conducted at the Cardiology OPD of Bir Hospital, National Academy of Medical Sciences, Kathmandu, Nepal. A total of 113 consecutive drug-naive hypertensive patients were enrolled. Demographic data including age, gender, and ethnicity were recorded. Blood pressure measurements were recorded and fasting lipid profiles (total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides) were collected in the subsequent visit. Data were analyzed using SPSS version 23. Results: The study included 53 males (46.9%) and 60 females (53.1%). The mean age distribution showed 38.1% young adults, 46.9% middle-aged, 13.3% elderly, and 1.8% very elderly patients. Mean systolic blood pressure was 157.62±11.755 mmHg and diastolic blood pressure was 96.73±10.556 mmHg. The mean values for lipids were- total cholesterol 184.77±41.51 mg/dL, HDL cholesterol 47.32±22.35 mg/dL, LDL cholesterol 111.84±38.49 mg/dL and triglycerides 165.20±78.60 mg/dL. A large proportion of patients had abnormal lipid levels, with elevated triglycerides and borderline HDL being the common pattern. Conclusion: A large proportion of drug-naive hypertensive patients demonstrated dyslipidemia, specifically elevated triglycerides and borderline HDL cholesterol. The coexistence of hypertension and dyslipidemia increases cardiovascular risk many-fold and requires comprehensive management strategies. Early detection and aggressive treatment of both conditions are essential to prevent future cardiovascular events.